Do Ordeals Work for Selection Markets? Evidence from Health Insurance Auto-Enrollment - Shepard, Mark; Wagner, Myles (American Economic Review, 2025)
Are application hassles, or “ordeals,” an effective way to limit public program enrollment? We provide new evidence by studying (removal of) an auto-enrollment policy for health insurance, adding an extra step to enroll. This minor ordeal has a major impact, reducing enrollment by 33 percent and differentially excluding young, healthy, and economically disadvantaged people. Using a simple model, we show adverse selection—a classic feature of insurance markets—undermines ordeals’ standard rationale of excluding low-value individuals since they are also low-cost and may not be inefficient. Our analysis illustrates why ordeals targeting is unlikely to work well in selection markets. (JEL D82, G22, H75, I13, I18)